AVALIAÇÃO DA TOXICIDADE SUBCRÔNICA IN VIVO DO EXOPOLISSACARÍDEO PRODUZIDO PELO FUNGO Lasiodiplodia theobromae MMPI - Túrmina, Janaína ângela (2012)
?-Glucans that are non-cellulosic have been considered as natural products that can be useful in preventing and treating several disease conditions in humans. Studies evaluating the toxicity caused by fungal exopolysaccharide (EPS) of the type ?(1->6)-D-glucan are scarce. This study evaluated the effects of subchronic treatments with EPS lasiodiplodan on toxicity, biochemical, hematological, and histopathological alterations. Thirty-two mice, 16 males and 16 females, were used in the study stratified into two groups; the treated group received EPS (50 mg/Kg) daily (28 days) via gavage and the control group received saline during the same period. Blood samples were collected via cardiac puncture for hematological and biochemical determinations. The liver, heart, kidneys, and spleen were collected for histopathological analysis. The statistical analysis was performed through one-way analysis of variance and only P < 0.05 Fvalues are presented. Significant reduction in blood glucose in males (35%; P< 0.01), transaminases activity in both sex (AST and ALT; 40%; P< 0.05), and urea (20%; P< 0.01) in females, were observed with the treatment using EPS. The results showed that sub-chronic treatments with EPS did not generate hematological and histopathological alterations. In conclusion, the study showed that the intake of EPS (? 1à6 D-glucan) did not produced any sign of toxicity in mice, independent of gender.